Thin film with high thermal conductivity and high insulating property and preparation method thereof
The thickness and pore size of the PTFE fiber layer are regulated through electrospinning technology, and combined with the thermally conductive powder to build a three-layer structure, which solves the problems of flexibility and thermal conductivity of the existing high thermal conductivity film materials, and achieves the unity of high thermal conductivity and high insulation performance.
Patent Information
- Application Number
- CN202411939642.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
The existing high-thermal conductivity and high-insulating films have lost flexibility under high filling amounts, and the thermal conductivity efficiency cannot meet the high-thermal conductivity needs, and cannot withstand high voltage breakdown.
Electrospinning technology is used to regulate the thickness and pore size of the PTFE fiber layer during PTFE fibrosis, so that it is composited with the thermally conductive powder to build a three-layer structure: the intermediate layer is a thermally conductive layer, and the upper and lower layers are non-densified PTFE wire mesh layer.
It achieves the unity of high thermal conductivity and high insulation performance, while maintaining the high and low temperature resistance and voltage resistance of PTFE, solving the problems of flexibility and thermal conductivity of traditional thermal film materials.
Smart Images

Figure CN119820980A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermally conductive films, and in particular to a film with high thermal conductivity and high insulation performance and a preparation method thereof. Background Art
[0002] Thermal conductive materials are widely used in many fields, including thermal conduction of semiconductor devices: they can help disperse and discharge the heat generated when the device is running, ensuring stable operation of the device; consumer electronics: high thermal conductivity materials can improve the heat dissipation performance of the device and extend its service life; high-power devices in communication base stations require efficient heat dissipation solutions; power batteries: batteries used in electric vehicles and energy storage devices require efficient heat dissipation systems, etc.
[0003] At present, the preparation of high thermal conductivity and high insulation film materials is to physically mix thermal conductive powders with various substrates. When a certain amount of thermal conductive powder is added, a thermal conductive path is formed. The substrates include but are not limited to silicone, polyurethane resin, rubber, etc. This type of synthesis method causes uneven dispersion of thermal conductive powders, and the addition amount is generally more than 90% to form effective thermal conductivity. However, due to the high proportion of filled thermal conductive powders, this type of film material loses its flexibility, becomes hard and brittle and easy to break. Even if a more flexible substrate such as silicone is used, although better film flexibility can be achieved at a high filling amount, the thermal conductivity efficiency still cannot meet the high thermal conductivity requirements in current application scenarios such as energy devices and IGBT packaging.
[0004] In addition, compared with the traditional method of preparing thermal conductive film by directly filling powder into the substrate and dispersing it, although the filling amount is already very high, the substrate is still a continuous phase, which will cause this type of thermal conductive film to be unable to withstand high voltage breakdown and is often limited in application.
[0005] It is difficult for thermally conductive polymer composite materials based on existing technologies to achieve the unity of high thermal conductivity and flexibility, because the thermal conductivity of thermally conductive materials is greatly affected by the filling ratio of thermally conductive powders. Thermally conductive powders are generally composed of inorganic powders such as alumina and boron nitride or metal powders such as copper powder and silver powder. Although the former has a high thermal conductivity, the filling amount is limited, otherwise the hardness and brittleness of the film will be greatly increased. The latter not only has a limited filling amount, but the conductive properties of the metal also limit the insulation properties of its thermally conductive film. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity and high insulation film and a preparation method thereof. The electrostatic spinning technology is used to adjust the thickness and pore size of the PTFE fiber layer during the PTFE fiberization process so that the PTFE fiber layer is compounded with the thermal conductive powder in the middle from the upper and lower surfaces. The middle layer is a thermal conductive layer, and the upper and lower layers are non-dense PTFE mesh layers. The three-layer structure constructed enables the film prepared by the present invention to maintain the excellent high and low temperature resistance and extremely strong insulation resistance of PTFE, while providing a thermal conductive path in the Z-axis direction, and having high thermal conductivity.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] First, the present invention provides a method for preparing a high thermal conductivity and high insulation film, comprising the following steps: placing a polytetrafluoroethylene spinning solution in an electrospinning device for electrospinning to form a first PTFE nanowire mesh layer; spraying a thermal conductive powder dispersion on the surface of the first PTFE nanowire mesh layer to form a thermal conductive layer; then continuing to electrospin the polytetrafluoroethylene spinning solution on the surface of the thermal conductive layer to form a second PTFE nanowire mesh layer; and finally hot pressing and aging to obtain a high thermal conductivity and high insulation film.
[0009] Further, the thickness of the first PTFE nanomesh layer is 10-30 μm, and the average pore size is 200-450 nm; preferably, the thickness of the first PTFE nanomesh layer is 13-25 μm, and the average pore size is 250-380 nm; more preferably, the thickness of the first PTFE nanomesh layer is 15-18 μm, and the average pore size is 270-350 nm.
[0010] Furthermore, the thickness of the second PTFE nanomesh layer is 10-30 μm, and the average pore size is 200-450 nm; preferably, the thickness of the second PTFE nanomesh layer is 13-25 μm, and the average pore size is 250-380 nm; more preferably, the thickness of the second PTFE nanomesh layer is 15-18 μm, and the average pore size is 270-350 nm.
[0011] Furthermore, the thickness of the heat-conducting layer is 90-170 μm.
[0012] Furthermore, the tetrafluoroethylene spinning solution is composed of a polytetrafluoroethylene aqueous dispersion and a spinning aid solution, and the mass ratio of the polytetrafluoroethylene aqueous dispersion to the spinning aid solution is 10-50:1, preferably 20-30:1, and more preferably 10-15:1.
[0013] Further, the concentration of the polytetrafluoroethylene aqueous dispersion is 50-80wt%, and the average particle size of the polytetrafluoroethylene in the polytetrafluoroethylene aqueous dispersion is 50-350nm; preferably, the concentration of the polytetrafluoroethylene aqueous dispersion is 60-70wt%, and the average particle size of the polytetrafluoroethylene is 150-180nm.
[0014] Furthermore, the spinning aid solution is at least one of a PVA aqueous solution, a polyanion sodium alginate (SA) aqueous solution, a chitosan aqueous solution, and a polyethylene oxide (PEO) aqueous solution.
[0015] Furthermore, the concentration of the spinning aid solution is 1-15wt%, preferably 2-10wt%, and more preferably 4-6wt%.
[0016] Furthermore, the thermally conductive powder dispersion is formed by dispersing thermally conductive powder in water, the concentration of the thermally conductive powder dispersion is 10-50wt%, and the thermally conductive powder is at least one of boron nitride, aluminum oxide, aluminum nitride, artificial diamond, silicon nitride, and graphene.
[0017] Further, the average particle size of the thermally conductive powder is 1-200 μm, preferably, the average particle size of the thermally conductive powder is 20-150 μm, and more preferably, the average particle size of the thermally conductive powder is 40-60 μm.
[0018] Furthermore, the electrospinning step is: fix the syringe containing polytetrafluoroethylene spinning solution to the spinning machine injection pump, install a 20G (1 / 2 inch, flat) stainless steel needle, connect the needle to the positive electrode of the high-voltage power supply, connect the receiving roller to the negative electrode of the high-voltage power supply, and stick release paper on the roller; the receiving distance of the electrospinning is 15-20cm, the liquid supply speed is 2mL / h, the roller speed is 300 rpm, the slide stroke is 20cm, and the spinning voltage is positive 15kV and negative 5kV.
[0019] Furthermore, the hot pressing aging is aging in a flat hot press, the aging temperature is 250-500°C, and the aging pressure is 0.5-5Mpa; preferably, the aging temperature is 300-450°C, and the aging pressure is 1-3MPa; more preferably, the aging temperature is 360-400°C, and the aging pressure is 2-2.5MPa.
[0020] Secondly, the present invention also provides a high thermal conductivity and high insulation film, which is prepared by the above-mentioned preparation method of the high thermal conductivity and high insulation film.
[0021] PTFE is also known as the "plastic king" among fluoropolymers, and has many excellent properties. For example, it has excellent high and low temperature resistance. PTFE can be used for a long time at -180 degrees to 260 degrees, and its basic performance remains unchanged; it has extremely strong insulation resistance, and the dielectric strength of PTFE can reach 10KV / MM; it is rare and non-flammable, and the limited oxygen index of PTFE is below 90%, and the flame retardant grade is UL V-0. In addition, PTFE is a corrosion-resistant material with excellent corrosion resistance. Except for molten alkali metals, it basically does not react with any chemical reagents. Its excellent aging resistance also allows PTFE to be exposed to the atmosphere for a long time, and its surface and performance can remain unchanged. At the same time, the friction coefficient of the PTFE surface can reach as low as 0.04, which has the lowest surface energy among solid materials.
[0022] One technical advantage of the present invention is that the present invention adopts electrostatic spinning technology, and by adjusting the thickness and pore size of the PTFE fiber layer, the PTFE can be compounded with the heat-conducting powder in the middle from the upper and lower surfaces. The film prepared according to the present invention not only maintains the excellent high and low temperature resistance, extremely strong insulation resistance (PTFE dielectric strength can reach 10KV / MM), and rare non-flammability (PTFE's limited oxygen index is below 90%, and the flame retardant grade is UL V-0) of PTFE. In addition, PTFE is a corrosion-resistant material with excellent corrosion resistance. Except for molten alkali metals, it basically does not react with any chemical reagents, which is also incomparable to the current thermal conductive films, thermal conductive gaskets, etc.
[0023] Another technical advantage of the present invention is that the thermally conductive powder is confined in the inner layer of the mesh structure by the PTFE fiber layer, there is no supporting substrate between the thermally conductive particles, the film is supported by the upper and lower layers of mesh PTFE, and the thermally conductive powder particles are in direct contact, which easily forms a heat conduction path, thereby improving the thermal conductivity without causing a decrease in insulation performance.
[0024] The technical concept of the present invention is to construct a three-layer structure, the middle layer is a thermal conductive layer, and the upper and lower layers are non-dense PTFE wire mesh layers. The upper and lower mesh structures leave a thermal conductive path in the Z-axis direction, which cannot be achieved by traditional dense layers or mixed preparation methods. In addition, the upper and lower mesh structures fix the middle thermal conductive powder layer, not only does it not lose its flexibility, but the PTFE in the wire mesh layer also provides a higher voltage resistance level.
[0025] The manufacturing process of the present invention is simple, fast and highly uniform, while ensuring that the thermally conductive powder material can be evenly deposited to form a more stable and unobstructed thermal conductive path, ensuring a high thermal conductivity coefficient in the Z-axis direction, and completely solving the key constraint factor of the low dispersed filling ratio of the thermally conductive powder of traditional thermally conductive gaskets or thermally conductive films. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1Schematic diagram of the preparation route of the high thermal conductivity and high insulation film of the present invention. DETAILED DESCRIPTION
[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0028] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be purchased from the market.
[0029] Example 1
[0030] Selecting polytetrafluoroethylene with a particle size range of 160 nm, dispersing it in water to form a polytetrafluoroethylene aqueous dispersion with a concentration of 70 wt %;
[0031] Dispersing PVA in water to form a spinning aid solution with a concentration of 5 wt%;
[0032] The polytetrafluoroethylene aqueous dispersion and the spinning aid solution are uniformly mixed in a mass ratio of 15:1 to form a polytetrafluoroethylene spinning solution;
[0033] Dispersing aluminum nitride in water to form a thermally conductive powder dispersion with a concentration of 30 wt %;
[0034] The syringe containing polytetrafluoroethylene spinning solution is fixed to the spinning machine injection pump, and a 20G (1 / 2 inch, flat) stainless steel needle is installed. The needle is connected to the positive electrode of the high-voltage power supply, and the receiving roller is connected to the negative electrode of the high-voltage power supply. Release paper is pasted on the roller; the receiving distance of the spinning machine is adjusted to 15-20cm, the liquid supply speed is 2mL / h, the roller speed is 300 rpm, the slide stroke is 20cm, the spinning voltage is positive 15kV, negative 5kV, the ambient temperature is 35°C, and the ambient humidity is 40%. Under the action of the high-voltage electric field, the solution is regularly sprayed on the electrospinning receiver through the spinneret The thermally conductive powder dispersion is sprayed and deposited on the surface of the first PTFE nano-wire mesh, and the solvent is dried to form a thermally conductive layer with a thickness of 150 μm. The tetrafluoroethylene spinning solution is then electrospun on the surface of the thermally conductive layer (i.e., forming a second PTFE nano-wire mesh layer), and the thickness of each polytetrafluoroethylene filament layer is controlled to be 15 μm. Finally, the film is hot-pressed and aged with a flat-plate hot press at a temperature of 400°C and a pressure of 2 MPa to obtain a high thermal conductivity and high insulation film with a thickness of 180 μm.
[0035] The preparation methods of Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are consistent with those of Example 1, and the differences are shown in Table 1. The preparation method of Comparative Example 3 is consistent with that of Example 1, and the difference is that the final hot pressing and aging in a flat hot press machine is not performed in Comparative Example 3. The specific contents of the above embodiments and comparative examples are shown in Table 1.
[0036] Table 1
[0037]
[0038] The products prepared in Examples 1-3 were subjected to performance tests on thermal conductivity, thermal resistance and insulation. The test results are shown in Table 1:
[0039] Table 1
[0040]
[0041] From the test data of Examples 1 to 3 and Comparative Examples 1 and 2, it can be seen that as the thickness of the PTFE nano-wire mesh layer increases, its pore size gradually decreases. When the thickness increases from 10 μm to 30 μm, the pore size of the PTFE nano-wire mesh layer gradually decreases. When the thickness is greater than 30 μm, its pore size range is less than 200 nm, the heat conduction path in the Z-axis direction will be blocked, and the thermal conductivity will gradually decrease. When the thickness is less than 10 μm, its pore size range is greater than 500 nm, the heat-conducting powder with a smaller particle size will pass through the PTFE mesh on both sides, causing the final heat-conducting film to produce powder falling phenomenon, which not only affects the thermal conductivity, but also reduces the insulation performance. Relative to the embodiment, the film obtained in Comparative Example 3 is not subjected to hot pressing and aging, and there is a gap between the heat-conducting powder, resulting in the obstruction of the heat conduction path and the decrease of thermal conductivity. At the same time, the spinning aid is not decomposed, and the three-layer structure of the outer polytetrafluoroethylene mesh and the inner heat-conducting powder cannot be effectively formed. The PTFE fiber layer is not sufficiently restrained to the heat-conducting powder, resulting in the decrease of insulation performance and thermal conductivity. In the present invention, the hot pressing process is a necessary process for making the powder compaction density higher and reducing the porosity in the process of forming a film. It should be noted that the pressure in the hot pressing process should not be too high, which will cause the particles of the powder layer to be crushed, which will in turn cause the thermal conductivity to decrease and make the "powder falling" phenomenon serious. The pressure is preferably 0.5-5Mpa.
[0042] The present invention uses an electrostatic spinning device to spray an aqueous solution of polytetrafluoroethylene (PTFE) on a release paper, and then sprays and deposits a dispersion of a high thermal conductivity powder on the surface of the polytetrafluoroethylene filament. After drying the solvent, the organic solution of PTFE is continued to be sprayed on its surface. The obtained three-layer structure film based on the high thermal conductivity powder is composed of PTFE nano-wire mesh on both sides of the inner core. After ripening under hot pressing, a high thermal conductivity insulating film is obtained. The present invention uses polytetrafluoroethylene as the outer layer of the thermal conductive insulating film, and electrostatic spinning makes it have a nanoporous structure, which ensures that the thermal conductive path of the outer layer of the film is unblocked. The inner core of the film adopts a powder material with a micron-level high thermal conductivity coefficient, which not only ensures that the powder is completely "confined" in the inner layer by the nano-mesh formed by the polytetrafluoroethylene wire, but also reduces the cost of the powder. Finally, the thermal conductive powder of the inner core is compacted and turned on by a hot pressing process, and the outer layer of polytetrafluoroethylene spinning aid is thermally decomposed to form a three-layer structure of an outer layer of polytetrafluoroethylene wire mesh and an inner layer of thermal conductive powder. Due to the difference between the particle size of the thermally conductive powder and the aperture of the polytetrafluoroethylene screen, the thermally conductive film disclosed in the present invention will not only not have the powder falling phenomenon caused by the traditional "filler powder" film, but also there is no "supporting agent" or "base material" of the traditional filling thermally conductive material inside the thermally conductive powder, so it has higher thermal conductivity.
[0043] According to the disclosure of the above description, those skilled in the art to which the present invention belongs may also make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A method for preparing a high thermal conductivity and high insulation film, characterized in that: The method comprises the following steps: placing polytetrafluoroethylene spinning solution in an electrospinning device for electrospinning to form a first PTFE nanowire mesh layer; spraying a heat-conducting powder dispersion on the surface of the first PTFE nanowire mesh layer to form a heat-conducting layer; then continuing to electrospin the polytetrafluoroethylene spinning solution on the surface of the heat-conducting layer to form a second PTFE nanowire mesh layer; and finally hot pressing and aging to obtain a high-thermal-conductivity and high-insulation film. The thickness of the first PTFE nanowire mesh layer is 10-30 μm, and the average pore size is 200-450 nm; The thickness of the second PTFE nanowire mesh layer is 10-30 μm, and the average pore size is 200-450 nm.
2. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The thickness of the first PTFE nanowire mesh layer is 13-25 μm, and the average pore size is 250-380 nm; The thickness of the second PTFE nanowire mesh layer is 13-25 μm, and the average pore size is 250-380 nm; The thickness of the heat conducting layer is 90-170 μm.
3. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The tetrafluoroethylene spinning solution is composed of a polytetrafluoroethylene aqueous dispersion and a spinning aid solution, and the mass ratio of the polytetrafluoroethylene aqueous dispersion to the spinning aid solution is 10-50:
1.
4. The method for preparing a high thermal conductivity and high insulation film according to claim 3, characterized in that: The concentration of the polytetrafluoroethylene aqueous dispersion is 50-80wt%, and the average particle size of the polytetrafluoroethylene in the polytetrafluoroethylene aqueous dispersion is 50-350nm.
5. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The spinning aid solution is at least one of a PVA aqueous solution, a polyanion sodium alginate aqueous solution, a chitosan aqueous solution, and a polyethylene oxide aqueous solution, and the concentration of the spinning aid solution is 1-15wt%.
6. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The thermally conductive powder dispersion is formed by dispersing thermally conductive powder in water. The concentration of the thermally conductive powder dispersion is 10-50wt%. The thermally conductive powder is at least one of boron nitride, aluminum oxide, aluminum nitride, artificial diamond, silicon nitride, and graphene.
7. The method for preparing a high thermal conductivity and high insulation film according to claim 6, characterized in that: The average particle size of the thermally conductive powder is 1-200 μm.
8. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The receiving distance of the electrospinning is 15-20 cm, the liquid supply speed is 2 mL / h, the roller speed is 300 rpm, the slide stroke is 20 cm, and the spinning voltage is positive 15 kV and negative 5 kV.
9. The method for preparing a high thermal conductivity and high insulation film according to claim 1, characterized in that: The hot pressing aging is aging using a flat hot press, the aging temperature is 250-500° C., and the aging pressure is 0.5-5 MPa.
10. A high thermal conductivity and high insulation film, characterized in that: The high thermal conductivity and high insulation film is prepared by the method for preparing the high thermal conductivity and high insulation film according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of multilayer sandwich type electrostatic-spinning polymer nanofiber composite membrane
CN103481624A
Preparation method for vertically oriented boron nitride / high polymer insulating heat conducting material
CN106832877A
Preparation method of insulating, heat-conducting and soaking film based on electrostatic spinning technology
CN114717754A
Preparation method of high-insulation and high-thermal-conductivity polymer-based composite material
CN114855367A
Radiation-resistant breathable film as well as preparation method and application thereof
CN116118304A